Transition Metal-Catalyzed Tandem Reactions of Ynamides for Divergent N-Heterocycle Synthesis - Hong, Feng-Lin; Ye, Long-Wu (Accounts of chemical research, 2020)
ConspectusYnamides are electron-rich heteroatom-substituted alkynes with a C-C triple bond directly attached to the amide group. Importantly, this amide group is able to impose an electronic bias, thus resulting in the highly regioselective attack of this polarized alkyne by a large variety of nucleophiles. Over the past two decades, catalytic reactions of ynamides have experienced dramatic developments, especially those catalyzed by transition metals. As a result, ynamides have been widely applied to the rapid and efficient assembly of versatile structurally complex N-containing molecules, especially in an atom-economic and stereoselective way.On the basis of newly developed ynamide preparations and new alkyne transformations, we first developed oxidation-initiated tandem reactions of ynamides such as zinc-catalyzed ynamide oxidation/C-H functionalization and copper-catalyzed ynamide oxidation/carbene metathesis, leading to divergent synthesis of isoquinolones, β-carbolines, and pyrrolo[3,4-c]quinolin-1-ones. Importantly, this protocol represents the first non-noble-metal-catalyzed intermolecular oxidation of alkynes by N-oxide type oxidants, and the related overoxidation could be dramatically inhibited in this non-noble-metal catalysis. Then, we achieved gold-catalyzed amination-initiated tandem reactions of ynamides via α-imino gold carbenes for efficient construction of various 2-aminoindoles, 3-amino-β-carbolines, and 2-aminopyrroles, where two new types of nitrene transfer reagents (benzyl azides and isoxazoles) were discovered. In particular, the use of isoxazoles as nitrene transfer reagents for atom-economic generation of α-imino metal carbenes has also been elegantly exploited by Hashmi, Liu, and many other groups, providing ready access to a wide range of functionalized N-heterocycles. Moreover, we revealed that donor/donor copper carbenes could be generated via copper-catalyzed diyne cyclization under mild conditions. These novel copper carbenes could undergo asymmetric C-H insertion, cyclopropanation, and formal [3 + 2] cycloaddition to produce diverse chiral polycyclic pyrroles with good to excellent enantioselectivities. Thus, this strategy may open new avenues in catalytic asymmetric reaction of ynamides, which remain largely unexplored and deserve more attention. Meanwhile, we also accomplished the efficient and practical synthesis of medium-sized lactams by yttrium-catalyzed cascade cyclization of allyl alcohol-tethered ynamides and the combination of radical chemistry based on visible-light photoredox catalysis with ynamide chemistry for divergent synthesis of useful 2-benzhydrylindoles and 3-benzhydrylisoquinolines.In this Account, we describe a panoramic picture of our recent contributions since 2015 to the development and application of ynamide chemistry in organic synthesis via transition metal-catalyzed tandem reactions by focusing on the tetrafunctionalization of ynamides. These studies provide not only efficient and attractive methods for divergent synthesis of valuable N-heterocycles but also some new insights into the exploration of alkyne chemistry and metal carbene chemistry.ConspectusYnamides are electron-rich heteroatom-substituted alkynes with a C-C triple bond directly attached to the amide group. Importantly, this amide group is able to impose an electronic bias, thus resulting in the highly regioselective attack of this polarized alkyne by a large variety of nucleophiles. Over the past two decades, catalytic reactions of ynamides have experienced dramatic developments, especially those catalyzed by transition metals. As a result, ynamides have been widely applied to the rapid and efficient assembly of versatile structurally complex N-containing molecules, especially in an atom-economic and stereoselective way.On the basis of newly developed ynamide preparations and new alkyne transformations, we first developed oxidation-initiated tandem reactions of ynamides such as zinc-catalyzed ynamide oxidation/C-H functionalization and copper-catalyzed ynamide oxidation/carbene metathesis, leading to divergent synthesis of isoquinolones, β-carbolines, and pyrrolo[3,4-c]quinolin-1-ones. Importantly, this protocol represents the first non-noble-metal-catalyzed intermolecular oxidation of alkynes by N-oxide type oxidants, and the related overoxidation could be dramatically inhibited in this non-noble-metal catalysis. Then, we achieved gold-catalyzed amination-initiated tandem reactions of ynamides via α-imino gold carbenes for efficient construction of various 2-aminoindoles, 3-amino-β-carbolines, and 2-aminopyrroles, where two new types of nitrene transfer reagents (benzyl azides and isoxazoles) were discovered. In particular, the use of isoxazoles as nitrene transfer reagents for atom-economic generation of α-imino metal carbenes has also been elegantly exploited by Hashmi, Liu, and many other groups, providing ready access to a wide range of functionalized N-heterocycles. Moreover, we revealed that donor/donor copper carbenes could be generated via copper-catalyzed diyne cyclization under mild conditions. These novel copper carbenes could undergo asymmetric C-H insertion, cyclopropanation, and formal [3 + 2] cycloaddition to produce diverse chiral polycyclic pyrroles with good to excellent enantioselectivities. Thus, this strategy may open new avenues in catalytic asymmetric reaction of ynamides, which remain largely unexplored and deserve more attention. Meanwhile, we also accomplished the efficient and practical synthesis of medium-sized lactams by yttrium-catalyzed cascade cyclization of allyl alcohol-tethered ynamides and the combination of radical chemistry based on visible-light photoredox catalysis with ynamide chemistry for divergent synthesis of useful 2-benzhydrylindoles and 3-benzhydrylisoquinolines.In this Account, we describe a panoramic picture of our recent contributions since 2015 to the development and application of ynamide chemistry in organic synthesis via transition metal-catalyzed tandem reactions by focusing on the tetrafunctionalization of ynamides. These studies provide not only efficient and attractive methods for divergent synthesis of valuable N-heterocycles but also some new insights into the exploration of alkyne chemistry and metal carbene chemistry.